THE EFFECT OF ROLE PLAY METHOD TO IMPROVE STUDENTS’ SPEAKING SKILL FOR NURSING STUDY PROGRAM AT FIRST SEMESTER OF UNIVERSITAS AUDI INDONESIA - Roikestina Silaban (Jurnal Scientia, 2022)
The objective of this research are to investigate whether Role Play Method significantly effect to Improve Students’ Speaking Skill for Nursing Study Program at First Semester of Universitas Audi Indonesia. This study is an experimental research. The population of this study is the students of Nursing study program at first semester of Universitas Audi Indonesia. The number of students was 124 students and 62 students are taken as the sample. The first group is experimental group which is taught by applying role play method. While the second group is control group, it is taught without role play method. oral test is used, Pass the instrument for collecting the data. These test consisted of two types, namely pre-test and post-test. As the result of the test, t-observed was 8.10 and t-table was 1.671 (p:005) the result of the data analysis show that the value of t-table 8.10³ 1.671 (p:0.05). It means that hypothesis alternative (Ha) is accepted while the null hypothesis (Ho) is rejected, therefore it is concluded that role play method significantly affects on students’speaking skill. Based on the explanation above, this research can be chosen as one alternative in teaching learning process.